Deep dive into the foreign direct investment dynamics of RCEP member countries in Indonesia - Wicaksono, Katon; Yuanfen, Tu (International Journal Labs, 2023)
This study focuses on the complex dynamics of foreign direct investment (FDI) in the Regional Comprehensive Economic Partnership (RCEP) and its relationship with Indonesia. Looking back over 30 years reveals the dual role of RCEP member countries as FDI sources and beneficiaries. The study identifies various factors that compel RCEP countries to invest abroad, including profitability institutional and strategic incentives. This study examines Indonesia's attractiveness as a foreign direct investment destination, considering the country's significant needs, natural resources, strategic location, and improved ease of doing business and analyzing the transformative impact of the RCEP agreement's implementation on reducing trade barriers. The study foresees positive trends in FDI dynamics in Indonesia, which it attributes to the continued profitable growth and indigenous integration of RCEP countries. The focus is on the policy framework within the RCEP and the critical role of bilateral agreements, highlighting the importance of structural development in Indonesia. Challenges remain, especially in remote areas, and bureaucracy and policy capacity improvements are needed. This study provides comprehensive insights into the interconnected dynamics of foreign direct investment between RCEP member countries and Indonesia. This highlights the need to improve the investment environment, develop infrastructure and ensure policy coherence for Indonesia to realize its full potential for foreign direct investment under RCEP. These results have important implications for science, policymakers, and international economic actors.